Autoimmune hemolytic anemia (AIHA) associated with chronic lymphocytic leukemia in the current era of targeted therapy. (November 2016) - Molica, Stefano; Polliack, Aaron
Highlights: Targeted therapy has transformed the landscape of therapy of CLL. This novel scenario may influence the incidence of autoimmune AICs complicating CLL. An extensive review of the literature focusing mainly on AIHA is presented. The relationship between newer CLL therapies and AIHA are still matter of study. Abstract: In the past decade the introduction of targeted therapies has dramatically transformed the landscape of treatment for chronic lymphocytic leukemia (CLL). Whether this new therapeutic scenario will modify the current prevalence statistics and natural history of autoimmune cytopenias complicating CLL is still a matter of debate. Here we present a comprehensive review of the literature on this topic, with special emphasis on the incidence of autoimmune hemolytic anemia (AIHA). The potential to induce autoimmune cytopenia has been studied mostly with ibrutinib, a first- in-class bruton kinase (BTK) inhibitor, licensed for the treatment of relapsed/refractory high-risk CLL. Recent observations suggest that emergent AIHA occurring during therapy with ibrutinib is more an expression of CLL activity than an ibrutinib-mediated process. Since available information on AIHA occurring during and after therapy with small-molecule kinase inhibitors relies mainly on data collected from clinical trials, a close post- marketing surveillance is mandatory in order to improve our understanding of this topic.